Chapter Accoppiamenti giudiziosi. Professionismo militare e signoria rurale in Italia nei secoli XIV e XV - STORTI, Francesco (Reti Medievali E-Book, 2023)
Mercenarism and Lordship are deeply linked in the Italy of the 14th and 15th centuries. It is difficult to distinguish between these two realities. Equally, it is difficult to understand the social impact of the mercenary phenomenon in reference to the lordship (this is an original theme). This work aims to clarify these aspects, with the use of new interpretative categories for the analysis of the complicated dynamics through which the two phenomena influenced each other.